2015
DOI: 10.5539/gjhs.v8n8p50
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Hemodialysis Adequacy in Cohort of Iranian Patient with End Stage Renal Disease

Abstract: Background:There are many factors that can affect dialysis adequacy; such as the type of vascular access, filter type, device used, and the dose, and rout of erythropoietin stimulation agents (ESA) used. The aim of this study was investigating factors affecting Hemodialysis adequacy in cohort of Iranian patient with end stage renal disease (ESRD).Methods:This is a cross-sectional study conducted on 133 Hemodialysis patients referred to two dialysis units in Sistan-Baluchistan province in the cities of Zabol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
3
3
0
Order By: Relevance
“…The increase blood flow rate is associated with high dialysis adequacy. These results are consistent with the previous studies (6,23). Thereby, 15% to 20% increase in blood flow led to an increase in urea clearance followed by an increase in dialysis adequacy due to increased diffusion mechanism.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The increase blood flow rate is associated with high dialysis adequacy. These results are consistent with the previous studies (6,23). Thereby, 15% to 20% increase in blood flow led to an increase in urea clearance followed by an increase in dialysis adequacy due to increased diffusion mechanism.…”
Section: Discussionsupporting
confidence: 83%
“…The result of our study showed, dialysis adequacy was less than international targets (9), which is consistent with the results of different studies (6,8). The results of this study indicated, dialysis inadequacy in routine dialysis using conventional filters, blood flow and dialysate flow rate.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Disease duration and treatment period, increased hospitalization and therapy costs, mental status and social harms are among complexities affecting thalassemia patients and their families (11). Without the contribution of the patients, their treatment will not be enough effective and no satisfactory result will be obtained (12). Generally, the existence of a patient in a family provides the ground for the behavioral change of the family members and can naturally increase the family requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Renal osteodystrophy in chronic kidney disease (CKD) patients causes several significant problems, including cardiovascular complications, the leading cause of mortality in chronic kidney disease [1,5]. There are many studies in the world reporting different results.…”
Section: Introductionmentioning
confidence: 99%